Developing Early Childhood Character In The Digital Era: Transition From Society 5.0 To Society 6.0 - Amita Diananda; M Munir Waspada (Universitas Negeri Semarang, 2025)
The transition from Society 5.0 to Society 6.0 presents significant challenges and opportunities in shaping early childhood character. This article aims to explore how technological evolution, particularly artificial intelligence, the Internet of Things, and robotics, influences the values education of young children. Using a qualitative literature review with an analytical-descriptive approach, this study analyzed open-access sources from 2019 to 2024, complemented by key foundational theories. The findings highlight the need for a holistic strategy involving schools, families, communities, government, and industry in shaping future-ready character. Key thematic areas include digital literacy, ethical technology use, emotional intelligence, and collaborative synergy across sectors. The study proposes a conceptual framework that integrates human values with digital advancements to support sustainable, inclusive character development in early childhood. These insights are expected to serve as a foundation for policy, curriculum, and innovation in early childhood education in the Society 6.0 era.